REKAYASA PERANGKAT LUNAK PENJUALAN PULSA ELECTRIC BERBASIS SMS MENGGUNAKAN VISUAL BASIC 6.0 - Eva Yulianti; Tauvan Rusyiatno (ITP Press, 2013)
Expansion of information technology through computers in all fields requiring a better handling, the counter emerging issues such as the fiesta Communica-checking balances and the amount and cost of media required for the supply of blank-blank and report of the transaction process. Therefore, to facilitate the transaction